On-chip array of thermoelectric peltier microcoolers - Gonçalves, L. M. (2007)
This article reports on the theoretical modelling, the Finite Element Modelling (FEM) simulation, the fabrication process and preliminary results of the first on-chip thermoelectric microcooler array (64 pixels arranged in a 88 array), with each pixel independently controlled. This microcooler array uses co-evaporated V–VI compounds of Bi2Te3 and Sb2Te3 as thermoelectric layers, and can be fabricated using planar thin-film technology, lithography and wet etching on top of a silicon wafer, where the CMOS electronic circuits were previously made